Penerapan Mediasi Penal Sebagai Penyelesaian Perkara Kekerasan dalam Rumah Tangga (Perspektif Restorative Justice) - Sonia, Citra; Prakasa, Ragil Surya (Asosiasi Ide Bahasa Kepri, 2024)
Domestic Violence (KDRT) is still a problem that must be addressed by the Indonesian government, recorded according to the National Commission on Women in 2022 an increase of 18,261 cases, even though law enforcement officials have implemented the Republic of Indonesia Police Regulation Number 8 of 2021 concerning Handling Crimes Based on Restorative Justice. And the institution of the Prosecutor's Office, through the Regulation of the Prosecutor's Office of the Republic of Indonesia Number 15 of 2020 concerning Termination of Restorative Justice Prosecution. So it is necessary to analyze the urgency of restorative justice through penal mediation as a settlement of domestic violence cases in the perspective of restorative justice. This research uses a normative juridical method with a statutory approach. The results of the research are the procedures for implementing restorative justice through penal mediation in domestic violence cases carried out with the stages of the police report or complaint process by victims of domestic violence, finding post mortem evidence if physical violence has occurred, a statement of peace, a mutual agreement, and evidence of victim recovery. Meanwhile, in the scope of the prosecutor's office, the stages of the process of peaceful efforts, mutual agreement, fulfillment of justice, and issuance of a letter of termination of prosecution are carried out, and if the agreement is not fulfilled, the court process continues, and penal mediation is very important in domestic violence cases, because Law Number 23 of 2004 concerning the Elimination of Domestic Violence does not provide special rules for restorative justice, so that the rights of children affected by domestic violence cannot be fulfilled. Therefore, it is important to implement Police and Prosecutor's Office Regulations on handling criminal offenses based on restorative justice to create a win-win solution and fulfill justice for the dignity of each party involved.